ASSOCIATION ANALYSIS AND RULE MINING FOR EFFICIENT MYOCLONIC DISEASE PREDICTION - et al., C.Radha (International Journal of Advanced Science and Technology, 2019)
Association evaluation has end up one of the maximum distinctly used and studied techniques in data mining. The most important aspect of this method engages coming across the capable relationship and co-occurrence among gadgets within the information. Association guidelines are articulated in an IF-THEN propositional rule-based totally format. Researchers evolved masses of algorithms for locating frequent item sets and relationship procedure. This paper provides the substantial study of various Association Rule mining for proficient myoclonic disease prediction. This paper also analyses Association Rule Mining for proficient Myoclonic Disease Prediction by means of linear regression.